Vocational education and training in Germany : short description - (:unkn) unknown (Publications Office of the European Union, 2020)
This short description contributes to better understanding of vocational education and training (VET) in Germany by providing insight into its main features and highlighting system developments and current challenges. It is published during the German Presidency in the Council of the EU (second half of 2020). Learning on the job is traditional in German education. Work-based learning (WBL) features in most secondary and tertiary VET programmes and graduate employment is high. However, demographic changes and the attractiveness of academic education have reduced the appeal of upper secondary VET. To address this, new designations of professional bachelor and professional master emphasise equivalence to academic programmes. Transformations currently influencing VET require political responses. Digital and green economy transitions are already being addressed, with digitalisation emphasised in Covid-19 pandemic responses. Continuing VET is increasingly important, highlighted in the Qualification Opportunities Act (2019). (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; I 2.1 Deutschland; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungssteuerung; Bildungsfinanzierung; Bildungspersonal; Bundesrepublik Deutschland